A facile route to diverse assemblies by host–guest recognition1. Issue 19 (21st May 2015) - Zhou, Xing; Han, Songling; Zhang, Qixiong; Dou, Yin; Guo, Jiawei; Che, Ling; Li, Xiaohui; Zhang, Jianxiang
<x xml:space="preserve">Abstract</x> We report a host–guest strategy that can simultaneously realize assembly and therapeutic loading, affording superstructures with tunable size and multiple morphologies.